Effects of Temperature Changes, Air Velocities and Volume Fractions on the Single Droplet Evaporation Behaviors at High Ambient Temperatures / W. Manosroi - Manosroi, W. (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
This study is aimed to investigate the effects of temperature changes and air velocities on the evaporation behaviors of the single droplet single component (pentadecane C-15) and binary mixtures (pentadecane C-15 and dodecane C-12 at 3:1, 1:1 and 1:3 volume ratios) in a heated chamber at high ambient temperatures of 91-98, 110-118, 129-145 and 155-170°C. The effects of volume fractions on the binary mixture single droplet evaporation characterisitics are also evaluated. The droplet diameter is measured at the forward scattering region. The time dependent changes of the droplet diameters are calculated from the Morphology Dependent Resonances (MDRs) of the refractive index which are measured in the backward region. The evaporation rates of the droplet increased with increased ambient temperatures. There is no effect of ambient air velocities on the droplet evaporation rates, owing to the small relative velocities between the droplets and the air. For the single component droplets, the ambient temperature is the most influent parameter on droplet evaporation rates and evaporation rate changes. For the binary mixture droplets, the volume fraction is the most influent parameter on droplet evaporation rates and evaporation rate changes. The results from this study can be applied for a better understanding of the fuel droplet in the combustion chamber of the engines.